Applications - Språkbanken Text (University of Gothenburg, 2024)
Anonymised job applications. The corpus is protected, contact Lena Rogström (lena.rogstroem@svenska.gu.se) for more information and access.

Anonymiserade jobbansökningar. Korpusen är skyddad, kontakta Lena Rogström (lena.rogstroem@svenska.gu.se) för mer information och åtkomst.
Ansökningar
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik